2014
DOI: 10.3892/or.2014.3479
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin-induced ER stress regulates chemokine CCL5 expression and secretion via STAT3 followed by decreased transmigration of MCF-7 breast cancer cells

Abstract: Abstract. Chemokine C-C motif ligand 5 (CCL5) is an important marker related to the progression of breast cancer and is upregulated in cancer cells. However, the mechanism of the overexpression of CCL5 in tumours has not yet been clarified. The present study aimed to investigate the role of endoplasmic reticulum (ER) stress in regulating CCL5 expression and its relationship with signal transducer and activator of transcription 3 (STAT3). Meanwhile, the effect of tunicamycin, a classical ER stress inducer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In contrast, CCL5 function in low-grade gliomas has not been explored, and the impact of CCL5 function on glioma biology remains unclear. Whereas little is known about CCL5 in brain tumors, increased CCL5 expression has been reported in lung, prostate, melanoma, colorectal, and breast cancer [67] , [85] , [86] , [87] , [88] , where a positive correlation between increased CCL5 expression and disease progression was identified [89] , [90] . In addition, CCL5-expressing melanoma cells form increasingly aggressive tumors in a concentration-dependent fashion [91] , and Ccl5 increases the growth of breast cancer cells in vitro [92] .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, CCL5 function in low-grade gliomas has not been explored, and the impact of CCL5 function on glioma biology remains unclear. Whereas little is known about CCL5 in brain tumors, increased CCL5 expression has been reported in lung, prostate, melanoma, colorectal, and breast cancer [67] , [85] , [86] , [87] , [88] , where a positive correlation between increased CCL5 expression and disease progression was identified [89] , [90] . In addition, CCL5-expressing melanoma cells form increasingly aggressive tumors in a concentration-dependent fashion [91] , and Ccl5 increases the growth of breast cancer cells in vitro [92] .…”
Section: Resultsmentioning
confidence: 99%
“…Tunicamycin, a pharmacological ER stress inducer, can stimulate tumor cell apoptosis [ 17 , 18 ]. Therefore, it has been used to develop an anti-cancer drug [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that U-STAT3 can effectively compete with non-phosphorylated inhibitory κB (IκB) in binding with nuclear factor (NF)-κB to form a new transcription factor. The new transcription factor could induce the expression of CCL5 (Yang et al, 2005;Yang and Stark, 2008;Zhang et al, 2014). Therefore, we detect the expressions of phosphorylated STAT3, U-STAT3, and CCL5 in both MCF-7 cells and MCF-7/PTP1B shRNA cells by Western blot.…”
Section: Effect Of Ptp1b On the Production Of Ccl5mentioning
confidence: 99%